Assessment of functional capacity in women with fibromyalgia: direct and self-reported methods. DOI: 10.5007/1980-0037.2011v13n4p292 - Diogo Homann; Suelen Meira Goes; Luciana da Silva Timossi; Neiva Leite (Universidade Federal de Santa Catarina, 2011)
Fibromyalgia can limit activities of daily living (ADLs) performance and has a negative impact on the quality of life of these patients. The objective of this study was to evaluate the association between direct and indirect methods for the assessment of functional capacity and their relationship with some features of fibromyalgia. Thirty-eight women with a diagnosis of fibromyalgia participated in the study. Functional capacity was assessed by the Health Assessment Questionnaire (HAQ), distance in the six-minute walk test (6MWT), and handgrip strength (HGS). Pain was rated on a visual analog scale. The Fibromyalgia Impact Questionnaire (FIQ) was applied to assess the impact on quality of life. Body mass index and waist circumference were also evaluated. Pearson's correlation test was used for parametric data and Spearman's correlation test for nonparametric data. Multiple regressions were also performed. Pain intensity was high in the patients (median: 9.5). The 6MWT distance was correlated with HAQ score (r=-0.55, p<0.01) and HGS (r=0.34, p<0.01). Pain was correlated with HGS (r=-0.41, p<0.01), HAQ score (r=0.62, p<0.01), and FIQ (r =0.66, p<0.01). Pain intensity explained 40% of the variation in HAQ scores. This variation increased to 60% after inclusion of 6MWT distance. In conclusion, pain seems to compromise HGS, ADLs and quality of life in women with fibromyalgia. The lower performance in the 6MWT might be explained by high body mass index. Taking into account pain, the HAQ seems to be an appropriate tool for the assessment of functional capacity in women with fibromyalgia.